2017
DOI: 10.21037/cdt.2017.03.16
|View full text |Cite
|
Sign up to set email alerts
|

Delayed enhancement cardiac computed tomography for the assessment of myocardial infarction: from bench to bedside

Abstract: A large number of studies support the increasingly relevant prognostic value of the presence and extent of delayed enhancement (DE), a surrogate marker of fibrosis, in diverse etiologies. Gadolinium and iodinated based contrast agents share similar kinetics, thus leading to comparable myocardial characterization with cardiac magnetic resonance (CMR) and cardiac computed tomography (CT) at both first-pass perfusion and DE imaging. We review the available evidence of DE imaging for the assessment of myocardial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Immediately after coronary CT angiography, additional infusion of 0.5 mL/kg contrast material was performed for 60 seconds. In total, 1.4 mL/kg body weight of iodine (not exceeding 100 mL) was used as contrast material (19,20). The optimal late scanning timing after injection of contrast material has not been universally determined.…”
Section: Ct Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after coronary CT angiography, additional infusion of 0.5 mL/kg contrast material was performed for 60 seconds. In total, 1.4 mL/kg body weight of iodine (not exceeding 100 mL) was used as contrast material (19,20). The optimal late scanning timing after injection of contrast material has not been universally determined.…”
Section: Ct Examinationsmentioning
confidence: 99%
“…In investigating myocardial tissue characteristics, delayed gadolinium enhancement MRI has been widely used because of the high diagnostic performance in the detection and localization of LGE. On the other hand, previous studies have revealed that MDE CT helped accurately determine and quantify the spatial extent of acute and healed myocardial infarction and demonstrated diagnostic performances for detecting MDE by using single-energy CT (4,20). To date, some studies have demonstrated the detection of MDE in nonischemic cardiomyopathy (5-7), but the number of studies is limited.…”
Section: Mde Ct Pattern (Differentiation Between Ischemic and Nonischmentioning
confidence: 99%
“…Furthermore, the doses of highly concentrated iodine-based contrast agents used in animals to achieve acceptable results are much higher than those used in clinical practice. 46 Nuclear imaging, including positron emission tomography (PET) and single-photon emission tomography (SPECT) can distinguish non-viable scar, viable hibernating scar, and healthy myocardium by changes in metabolism and/or perfusion, but are hampered by a poor resolution. 47 Intracardiac echocardiography has been used to delineate scar based on wall-thinning, wall motion abnormalities, 48 and occasionally the heterogeneity in SI.…”
Section: Cardiac Imaging To Delineate Scar and Their Validation Usingmentioning
confidence: 99%
“…These techniques include delayed-enhancement CT and virtual monochromatic imaging. 46 Future CT scanners with dual energy sources will also likely reduce contrast load. 46 To improve imaging of the arrhythmogenic substrate there is a need for scanners with better spatial resolution.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation